Design and implementation of modular DC micro-grid for integration of battery energy storage and solar PV - Zhao, Zhenyu (2016)
With more and more electronic devices using DC power supply, DC micro-grid is playing an important role. Compared to conventional centralized AC system, DC micro-grid not only has higher conversion efficiency but also uses renewable energy sources (RESs). So, they are clean and sustainable compared with traditional fossil fuels. Usually, power generation of RESs is intermittent, it also has many LC components in a DC micro-grid. In order to maintain system’s reliability and reduce size and cost of LC components, a modular DC micro-grid was proposed. The modular DC micro-grid is such a grid which integrates multiple DC/DC converters, RESs and energy storage system (ESS) together. When the generation of RESs is larger than loads consumption, surplus energy is charged into ESS. When the generation of RESs is smaller than loads consumption, lack of energy is discharged by ESS. Thus, bus voltage can be constant with collaborative operations of RESs and ESS. Except it, multiple DC/DC converters share a set of LC components in a modular DC micro-grid, which increases utilization of LC components and reduce cost and size of them. In RESs, solar PVs and wind turbines are most common. Wind turbines are usually used in rural areas. However, this project is conducted in Singapore, which is a big city located in the equator. The sunlight of this area is very sufficient. Therefore, solar PVs were chosen as RESs. What is more, battery energy system (BES) was chosen as ESS. In this project, the modular DC micro-grid has three channels. The battery is used in channel one, solar PVs are used in channel two and channel three. One of the objects in this project is maintaining DC bus voltage stable. In order to achieve this goal, a monitoring bus (MB) algorithm was proposed. In addition, the output power of solar PVs is influenced by many factors, such as irradiance, temperature. It just has one maximum power point (MPP) in each condition. So, another object of this project is making solar PVs operate in MPP. In order to complete this object, improved maximum power point tracking (MPPT) algorithm was chosen. In MB algorithm, we chose double closed-loop PI control method whose inner loop is inductor current feedback loop and the external loop is DC bus voltage feedback loop. In MPPT algorithm, we took perturbation and observe (P&O) method. Considering control of current is better than control of power, another inductor current PI controller was added into the system to improve system’s control effect. Then, each channel was checked with these algorithms to ensure them can operate well. Finally, a modular DC micro-grid control method was proposed. From the results, this modular DC micro-grid could maintain DC bus voltage stable when solar PVs operate in MPPT mode, which increased system’s stability and reliability. In addition, it reduced the size and cost of the whole system. Key Words: Modular DC Micro-grid, MPPT Algorithm, P&D Method, MB Algorithm, PI controller.